2015
DOI: 10.1088/0004-637x/799/1/11
|View full text |Cite
|
Sign up to set email alerts
|

Alma Observations of Warm Dense Gas in NGC 1614—breaking of the Star Formation Law in the Central Kiloparsec

Abstract: We present ALMA Cycle-0 observations of the CO (6-5) line emission and of the 435 μm dust continuum emission in the central kiloparsec of NGC 1614, a local luminous infrared galaxy at a distance of 67.8 Mpc (1 = 329 pc). The CO emission is well resolved by the ALMA beam (0. 26 × 0. 20) into a circumnuclear ring, with an integrated flux of f = 898 (±153) Jy km s −1 , which is 63(±12)% of the total CO (6-5) flux measured by Herschel. The molecular ring, located between 100 pc < r < 350 pc from the nucleus, look… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 124 publications
(260 reference statements)
10
43
0
Order By: Relevance
“…The recent 0. 5-CO(2-1) map of the SMA, published by König et al (2013), spatially resolved the nuclear disk into an asymmetric ring of ∼230 pc radius, similar to the CO(6-5) image of the central region obtained with ALMA by Xu et al (2015). The disk shows an extension to the northwest in the SMA image.…”
Section: Ngc 1614supporting
confidence: 60%
See 3 more Smart Citations
“…The recent 0. 5-CO(2-1) map of the SMA, published by König et al (2013), spatially resolved the nuclear disk into an asymmetric ring of ∼230 pc radius, similar to the CO(6-5) image of the central region obtained with ALMA by Xu et al (2015). The disk shows an extension to the northwest in the SMA image.…”
Section: Ngc 1614supporting
confidence: 60%
“…In their multiwavelength study, Herrero-Illana et al (2014) concluded that there is no evidence of an AGN in the nucleus of NGC 1614 down to an AGN-to-bolometric luminosity ratio of <10%. In agreement with this picture, not detecting the nuclear source in the 435 µm continuum image of the galaxy obtained with ALMA led Xu et al (2015) to rule out a Compton-thick AGN in NGC 1614.…”
Section: Ngc 1614supporting
confidence: 53%
See 2 more Smart Citations
“…Several recent millimeter studies have been performed to determine the properties of the fuel of the star formation, i.e., the molecular gas, and its inflows and outflows (Olsson et al 2010;Imanishi & Nakanishi 2013;Xu et al 2015; García-Burillo et al 2015; König et al 2016;Saito et al 2016Saito et al , 2017. However, while the bulk of observational evidence favors a pure starburst scenario for NGC 1614, the existence of an intrinsically weak AGN at its very center has not yet been completely ruled out (Risaliti et al 2000;Wilson et al 2008;Pereira-Santaella et al 2015b).…”
Section: Introductionmentioning
confidence: 99%